1992
DOI: 10.1128/jb.174.22.7419-7427.1992
|View full text |Cite
|
Sign up to set email alerts
|

S-layer protein gene of Lactobacillus brevis: cloning by polymerase chain reaction and determination of the nucleotide sequence

Abstract: The surface (S)-layer protein of Lactobacillus brevis was isolated, purified, and characterized. The S-layer protein is the major protein of the cell, with an apparent molecular mass of 46 kDa in sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). Immunogold electron microscopy with polyclonal antiserum against the isolated 46-kDa protein was used to confirm the surface location of this protein. N-terminal amino acid sequences of the intact 46-kDa protein and its tryptic peptides were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
134
3
2

Year Published

1993
1993
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(144 citation statements)
references
References 37 publications
5
134
3
2
Order By: Relevance
“…In keeping with other S-layer subunit proteins (18,29,43,45), the vapA transcript expressed from the P1 promoter was found to be monocistronic. Indeed, only the Bacillus S-layers have been shown to be polycistronic (1).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In keeping with other S-layer subunit proteins (18,29,43,45), the vapA transcript expressed from the P1 promoter was found to be monocistronic. Indeed, only the Bacillus S-layers have been shown to be polycistronic (1).…”
Section: Discussionsupporting
confidence: 52%
“…Several other S-layer systems have multiple promoters; in these cases, however, primer extension experiments have shown that these promoters are active during growth in vitro. For example, three transcriptional start sites have been shown in front of the structural genes for the S-layers of Bacillus brevis 47, the P2 and P3 promoters being most active (1), while the Lactobacillus brevis S-layer protein gene possesses two promoters which appear to be equally active during exponential growth phase (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The secretion probe vector is based on the signal peptide sequence of the L. brevis surface layer protein SlpA (43) and the nuc gene for Staphylococcus aureus nuclease (37), devoid of its export signal (⌬ SP nuc). The SP slpA signal sequence (with PstI and AatII restriction sites added at the 5Ј and 3Ј ends) was amplified using the primers shown in Table 2, using chromosomal DNA of L. brevis as template.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the correlation between the level of expression and codon usage preference in lactobacilli, we have compared the cumulative codon usage values of NNC/U-type and NNG/A-type two-codon sets ofLactobacillus genes known to be efficiently expressed [e.g. S-layer proteins constitute 5-10% of total proteins (27,28), L-LDH represents >2% of soluble protein in lactobacilli (29)] with those of genes known or presumed to be inefficiently expressed (e.g. repA gene of plasmid p353-2, and xylB and xylR genes of L.pentosus (21,30), and the regulatory gene lacT from L. casei (31).…”
Section: Codon Usage In Lactobacillusmentioning
confidence: 99%